Integrating health and agriculture to maximize the nutritional impact of orange-fleshed sweetpotato: The Mama SASHA proof-of-concept project in Western Kenya - International Potato Center (2014)
The intervention phase of this project has been successfully completed, endline survey data have been collected and analysis for evaluation of impact is underway.